Empirical study of herding behavior impacts on South Asia Nation - Alom, Shahedin; Mohd Nasarudin, Ahmad Fawwaz (2019)
This paper investigates the dynamic relationship between Sri Lanka and Pakistan’s stock markets and its interdependent with India and China given the later hefty involvement in the former economic activity. The study investigate the potential macro herding across the four countries and also try to examine the spillover effect especially from superior market towards its developing counterpart. The Cross Sectional Absolute Deviation (CSAD) is utilized to test for herding and it suggested that while herding exist in China, Sri Lanka and Pakistan pre-crisis period, only Pakistan have herding after the subprime crisis. Testing industrial herding across the countries revealed that investors do not emphasize sectoral influence over herding decision. However, as we consider the spillover effects between countries and test for herding in selected industry with higher percentage of trade among them, it reveals herding existence in several diferent industry pre and post crisis. The findings confirms the existence of herding in individuals market except for India and also across market in selected industry due to spillover effects.